Extracellular matrix molecules and their potential contribution to the function of transplanted pancreatic islets - Llacua, L. Alberto (Diabetologia, 2018)
Extracellular matrix (ECM) molecules are responsible for structural and biochemical support, as well as for regulation of molecular signalling and tissue repair in many organ structures, including the pancreas. In pancreatic islets, collagen type IV and VI, and laminins are the most abundant molecules, but other ECM molecules are also present. The ECM interacts with specific combinations of integrin α/β heterodimers on islet cells and guides many cellular processes. More specifically, some ECM molecules are involved in beta cell survival, function and insulin production, while others can fine tune the susceptibility of islet cells to cytokines. Further, some ECM induce release of growth factors to facilitate tissue repair. During enzymatic isolation of islets for transplantation, the ECM is damaged, impacting islet function. However, restoration of the ECM in human islets (for example by adding ECM to the interior of immunoprotective capsules) has been shown to enhance islet function. Here, we provide current insight into the role of ECM molecules in islet function and discuss the clinical potential of ECM manipulation to enhance pancreatic islet function and survival. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-017-4524-8) contains a slideset of the figures for download, which is available to authorised users.